THE ROLE OF SOIL IN HUMAN LIFE AND MEASURES TO PREVENT ITS POLLUTION - Nurov Sarboz Azim o’g’li (World Scientific Research Journal, 2025)
Abstract Soil is a fundamental resource for human survival and environmental sustainability. It serves as the foundation for agriculture, water filtration, and biodiversity. However, the increasing rates of soil pollution caused by industrial activities, agricultural chemicals, and improper waste disposal pose significant threats to ecosystems and human health. This article explores the essential role of soil in human life, identifies the primary causes of soil pollution, and proposes effective prevention strategies. Implementing sustainable agricultural practices, stricter industrial regulations, and public awareness campaigns are crucial steps in maintaining soil health for future generations.